Odpowiedź :
Odpowiedź:
2³*4²*8=2³*2⁴*2³=2³⁺⁴⁺³=2¹⁰
b)
27*9³*3=3³*3⁶*3¹=3³⁺⁶⁺¹=3¹⁰
c)
(2³)²*4³/8³=2⁶*2⁶/2⁹=2⁶⁺⁶⁻⁹=2³
d)
(9²)²*27/3⁵=3⁸*3³/3⁵=3⁸⁺³⁻⁵=3⁶
Szczegółowe wyjaśnienie:
[tex]a) \ 2^{3}\cdot4^{2}\cdot8 = 2^{3}\cdot(2^{2})^{2} \cdot2^{3} = 2^{3}\cdot2^{4}\cdot2^{3}=2^{3+4+3} = 2^{10}\\\\b) \ 27\cdot9^{3}\cdot3 = 3^{3}\cdot(3^{2})^{3}\cdot3 = 3^{3}\cdot3^{6}\cdot3 = 3^{10}\\\\c) \ \frac{(2^{3})^{2}\cdot4^{3}}{8^{3}} = \frac{2^{6}\cdot(2^{2})^{3}}{(2^{3})^{3}} = \frac{2^{6}\cdot2^{6}}{2^{9}} = 2^{6+6-9} = 2^{3}\\\\d) \ \frac{(9^{2})^{2}\cdot27}{3^{5}} =\frac{((3^{2})^{2})^{2}\cdot3^{3}}{3^{5}} = \frac{3^{8}\cdot3^{3}}{3^{5}} = 3^{8+3-5} = 3^{6}[/tex]
Wyjaśnienie:
[tex]a^{m}\cdot a^{n} = a^{m+n}\\\\a^{m}:a^{n} = a^{m-n}\\\\(a^{m})^{n} = a^{m\cdot n}[/tex]